Safety analysis of omitting axillary lymph node dissection in early-stage breast cancer with 1–2 sentinel lymph nodes macro-metastases: a meta-analysis - Chen, Yu; Zhang, Xiaoming; Wu, Qingping; Gao, Shanshan; Wang, Lu; Zeng, Minxia; Gu, Lihu; Sheng, Changrui (Frontiers in Oncology, 2025)
BackgroundCurrently, the axillary management strategy of omitting axillary lymph node dissection (ALND) in early-stage breast cancer (BC) patients with cT1-2, clinically node-negative (cN0), and sentinel lymph node biopsy (SLNB) revealing 1–2 sentinel lymph nodes (SLNs) macro-metastases remains controversial. This study aims to systematically evaluate the safety of omitting ALND in this population.MethodsThis study was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines and was registered with the registration number: CRD42025645388. A systematic literature search was conducted across five electronic databases (PubMed, Web of Science, Cochrane Library, Ovid Medline, and Embase) from inception through December 2024. Randomized controlled trials (RCTs) and cohort studies meeting the predefined eligibility criteria were included. Primary outcomes included disease-free survival (DFS) and overall survival (OS). The association between ALND omission and long-term outcomes was assessed using pooled hazard ratios (HRs) with 95% confidence intervals (CIs).ResultsFifteen studies (6 RCTs, 9 cohort studies) involving 33,599 patients in the SLNB-only group and 95,711 controls receiving SLNB+ALND were analyzed. No significant differences in DFS (HR = 0.99, 95%CI:0.85-1.14, p=0.857) or OS (HR = 1.03, 95%CI: 0.92-1.14 p=0.251) were observed in both groups. Subgroup analyses by follow-up duration (5-years and 10-years), study design (RCTs and cohort studies), and region (Eastern and Western) showed no survival differences between the experimental and control groups. (all p values are greater than 0.05).ConclusionOmitting ALND is safe for early-stage BC patients with cT1-2, cN0, and 1–2 SLNs macro-metastases.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42025645388.